In vivo evaluation of combined CK2 inhibition and irradiation in human WiDr tumours - Zwicker, Felix; Hauswald, Henrik; Weber, Klaus-Josef; Debus, Jürgen; Huber, Peter E. (In vivo, 2021)
Background/Aim: Casein kinase 2 (CK2) which sustains multiple pro-survival functions in cellular DNA-damage response, is strictly regulated in normal cells but elevated in cancer. CK2 is considered as a potential therapeutic target, and its inhibition has been associated with radiosensitization in mammalian cells in vitro. Here, we investigated potential radiosensitization by CK2 inhibition in vivo. Materials and Methods: The effect of CK2 inhibition in vivo was investigated in human WiDr-xenograft tumours grown subcutaneously on BALB/c nu/nu mice with and without fractionated irradiation. CK2 inhibition was performed using the specific inhibitor tetra-bromobenzotriazole (TBB). Histological examinations included staining for apoptosis and double-strand breaks. Results: Both TBB treatment alone and radiation alone significantly reduced tumour growth, which was reflected by increased apoptosis rates. However, TBB treatment did not boost radiation-induced tumour growth suppression in combined treatment, although the apoptosis rate increased and repair of double-strand breaks was reduced. This was in stark contrast to previous data on in vitro radiosensitization. Conclusion: The absence of radiosensitization by CK2 inhibition should be investigated in different tumour models.
Gesehen am 23.02.2021